PENGARUH PENGGUNAAN AMPAS KELAPA (Cocos nucifera L) FERMENTASI DALAM RANSUM TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK BABI GROWER-FINISHER (Effect of fermented coconut (Cocos nucifera L) waste in ration on dry matter and organic matter.....) - Elfiana Elita Vilan; Ni nengah suryani; Tagu Dodu; I Made S. Aryanta (Universitas Nusa Cendana, 2023)
This research aimed to evaluate the effect of using fermented coconut waste (Cocos nucifera L) in the diet on the consumption and digestibility of dry matter and organic matter in grower-finisher pigs. Twelve castration landrace pigs aged 4-5 months with an initial weight of 50-83kg with an average of 66.25kg (KV = 15.75%) were used in this experiment. The experimental was was a Randomized Block Design (RBD) with four treatments and three replications. The treatments were R0: ration without fermented coconut waste (FCW), R1: ration using 5% FCW, R2: ration using 10% FCW, R3: ration using 15% FCW. The results showed that treatment had no significant effect (P>0.05) on the ration consumption, dry matter consumption, organic matter consumption, dry matter digestibility and organic matter digestibility. It can be concluded that coconut waste as much as 0%, 5%, 10% and 15% in the ration gave the same effect on ration consumption, dry matter consumption, organic matter consumption, dry matter digestibility and organic matter digestibility. Fermented coconut waste can be used up to 15% in grower-finisher pig rations.